Pyroelectric influence on lithium niobate during the thermal transition for cryogenic integrated photonics - Thiele, Frederik; Hummel, Thomas; Lange, Nina Amelie; Dreher, Felix; Protte, Maximilian; Bruch, Felix vom; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Materials for Quantum Technology)
Abstract Lithium niobate has emerged as a promising platform for integrated quantum optics, enabling efficient generation, manipulation, and detection of quantum states of light. However, integrating single-photon detectors requires cryogenic operating temperatures, since the best performing detectors are based on narrow superconducting wires. While previous studies have demonstrated the operation of quantum light sources and electro-optic modulators in LiNbO 3 at cryogenic temperatures, the thermal transition between room temperature and cryogenic conditions introduces additional effects that can significantly influence device performance. In this paper, we investigate the generation of pyroelectric charges and their impact on the optical properties of lithium niobate waveguides when changing from room temperature to 25 K, and vice versa. We measure the generated pyroelectric charge flow and correlate this with fast changes in the birefringence acquired through the Sénarmont-method. Both electrical and optical influence of the pyroelectric effect occur predominantly at temperatures above 100 K.
Keywords: General Earth and Planetary Sciences; General Environmental Science

„4 THe BoYZ“ – Widmungen im Szene-Graffiti aus konstruktionsgrammatischer Perspektive. Die multimodale Relator-Konstruktion als grammatische Musterbildung im Horizont des Textes - Tophinke, Doris; Dübbert, Alexander (Konstruktionsgrammatik X. Textsorten und Textmuster als Konstruktionen?)

Perspectives of children and young people on their education as preparing for their future in the digital age: In-depth qualitative study in five European countries. - Eickelmann, Birgit; Barbovschi, M.; Holmarsdottir, H.B.; Parsanoglou, D.; Sisask, M.; Labusch, Amelie (Understanding the everyday digital lives of children and young people)

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

WeGA-WebApp release 4.9.0 - Stadler, Peter; Schmidt, Jakob; Zheng, Xianghua; Ried, Dennis; Richts, Kristina; Schreiter, Solveig; Jakob, Charlene
WeGA-WebApp release 4.9.0 Main features replace external Beacon service #451 update csLink to version v2 #450 Changelog A detailed changelog can be found at https://github.com/Edirom/WeGA-WebApp/wiki/Changelog Full Changelog: v4.8.1...v4.9.0 License This work is available under dual license: BSD 2-Clause and Creative Commons Attribution 4.0 International License (CC BY 4.0)

A Comparative Kinetic and Computational Investigation of the Carbon‐Sulfur Cross Coupling of Potassium Thioacetate and 2‐Bromo Thiophene Using Palladium/Bisphosphine Complexes - Peschtrich, Sebastian; Schoch, Roland; Kuckling, Dirk; Paradies, Jan (European Journal of Organic Chemistry)
Abstract We conducted an investigation into the palladium‐catalyzed carbon‐sulfur cross‐coupling reaction involving a 2‐bromothiophene derivative and potassium thioacetate as a substitute for hydrogen sulfide. This investigation utilized kinetic and computational methods. We synthesized two palladium complexes supported by the bisphosphane ligands bis(diphenylphosphino)ferrocene (DPPF) and bis(diisopropylphosphino)ferrocene (D i PPF), as well as their tentative intermediates in the catalytic cycle. Reaction rates were measured and then compared to computational predictions.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of Ferrocenyl Boranes and their Application as Lewis Acids in Epoxide Rearrangements - Köring, Laura; Birenheide, Bernhard; Krämer, Felix; Wenzel, Jonas O.; Schoch, Roland; Brehm, Martin; Breher, Frank; Paradies, Jan (European Journal of Inorganic Chemistry)
A series of substituted ferrocenyl boron derivatives was synthesized. The oxidation of the ferrocenyl unit resulted in a significant increase of the boron‐centered Lewis acidity. The neutral and cationic Lewis acids were characterized by NMR‐spectroscopy, crystal structure analysis and by computational methods. The new Lewis acids were then applied in the Meinwald rearrangement of epoxides, predominantly furnishing aldehydes as the kinetic products.
Keywords: Inorganic Chemistry

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

From Swiss-cheese to discrete ferroelectric composites: assessing the ferroelectric butterfly shape in polarization loops - Myroshnychenko, Viktor; Mulavarickal Jose, Pious Mathews; Farheen, Henna; Ejaz, Shafaq; Brosseau, Christian; Förstner, Jens (Physica Scripta)
We explore the polarization hysteretic behaviour and field-dependent permittivity of ferroelectric-dielectric 2D materials formed by random dispersions of low permittivity inclusions in a ferroelectric matrix, using finite element simulations. We show how the degree of impenetrability of dielectric inclusions plays a substantial role in controlling the coercive field, remnant and saturation polarizations of the homogenized materials. The results highlight the significance of the degree of impenetrability of inclusion in tuning the effective polarization properties of such ferroelectric composites: coercive field drops significantly as percolation threshold is attained and remnant polarization decreases faster than a linear decay.
Keywords: tet_topic_ferro

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Time and Space Optimized Storage-based BIST under Multiple Voltages and Variations - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (European Test Symposium, The Hague, Netherlands, May 20-24, 2024)

Vmin Testing under Variations: Defect vs. Fault Coverage - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Latin American Test Symposium (LATS), Maceió, Brazil, April 9-12, 2024)

Functional Safety and Reliability of Interconnects throughout the Silicon Life Cycle - Hellebrand, Sybille; Sadeghi-Kohan, Somayeh; Wunderlich, Hans-Joachim (International Symposium of EDA (ISEDA), Xi'an, China, May 10-13, 2024)

Involvement of domain experts in the AI training does not affect adherence – An AutoML study - Lebedeva, Anastasia; Protte, Marius; van Straaten, Dirk; Fahr, René (Advances in Information and Communication)

Robust Test of Small Delay Faults under PVT-Variations - Wunderlich, Hans-Joachim; Jafarzadeh, Hanieh; Hellebrand, Sybille (International Symposium of EDA (ISEDA), Xi’an, China, May 10-13, 2024)

Modeling Crosstalk-induced Interconnect Delay with Polynomial Regression - Stiballe, Alisa; Reimer, Jan Dennis; Sadeghi-Kohan, Somayeh; Hellebrand, Sybille

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials